Monuments in the mountains: the megalithic graves of western China - Hein, A (Archaeopress, 2022)
While the megaliths of Europe are world-famous and the dolmens of Korea, Japan, and Northeast China have received much scholarly attention, few have heard of the stonebuilt graves of western China. Even scholars interested in stone graves in this region tend to focus on the small stone-cist graves located underground which are common throughout much of the Chinese border region. This paper draws attention to the largely overlooked above-ground grave structures made of large stones that can be found chiefly in Southwest China. These megalithic graves are peculiar in many ways, both within East Asia and in comparison to megalithic structures found world-wide. Other parts of East Asia (Northeast China, Korea, Japan, and parts of the southeastern Chinese coast) are characterized by dolmens, but dolmens do not appear in Southwest China. Here, structures that could be described as passage graves, barrows, and constructions similar to the Celtic cistvaens can be found. Cistvaen-like structures appear in various places on and along the eastern rim of the Tibetan Plateau, but the larger structures seem to be limited to the Anning River Valley and the surrounding mountains of southern Sichuan and northern Yunnan. This paper will briefly introduce the stone-built graves of western China and then focus on the only megalithic structures that can be found in the region, the megalithic graves of Southwest China. This region is extremely mountainous with lush greenery obstructing views of the monuments. The paper considers the distribution of the graves in relation to their natural environment and to each other, both spatially and in terms of usage patterns, suggesting possible connections as well as differences between them.